A Guide to the World Bank : Second Edition - World Bank (Washington, DC: World Bank, 2012)
Conceived in 1944 to reconstruct war-torn Europe, the World Bank Group has evolved into one of the world's largest sources of development assistance, with a mission of fighting poverty with passion by helping people help themselves. This book guides the reader into the conceptual work of the World Bank Group. Its goal is to serve as starting point for more in-depth inquiries into subjects of particular interest. It provides a glimpse into the wide array of activities in which the Bank Group institutions are involved, and it directs the reader toward other publications and to Web sites that have more detailed information. The following chapters explain how the World Bank Group is organized; how it operates; and how its work focuses on countries, regions, and specific topics in development. Appendixes provide further information on Bank Group contacts, on the organization's history, and on country membership and voting shares in the institutions.